Biochemical Changes in Fish Feeds and Ingredients during Storage - R., Anandan; O., Kavitha; Mathew, Suseela; P.G., Viswanathan Nair (Fishery Technology, 2025)
The changes in major biochemical components of three fish feeds (1000 Grower 15+, 3000 Grower and 6000 Grower A) and three feed ingredients (Indian fish meal, Danish fish meal and wheat flour) during storage for six months are reported. There was no significant change in total protein content either in fish feeds or their ingredients during the storage period. But a significant reduction in crude fat content was noticed in both feeds and ingredients upon storage. Histamine content! of feeds and their ingredients was found to be increasing till the fourth month of storage. Significant decline in the levels of various amino acids was also observed. Unsaturated fatty acids and most of the saturated fatty acids decreased in stored ingredients. But in feeds only a marginal decrease in the levels of unsaturated fatty acids was observed. The results indicate that storage considerably reduces the nutritive value of the feeds and at the same time produces toxic compounds such as biogenic amines.